2016
DOI: 10.1111/spc3.12255
|View full text |Cite
|
Sign up to set email alerts
|

Reputation, Gossip, and Human Cooperation

Abstract: Why do people cooperate? We address this classic question by analyzing and discussing the role of reputation: people cooperate to maintain a positive reputation in their social environment. Reputation is a key element fueling a system of indirect reciprocity, where cooperators establish a good reputation and are thus more likely to receive future benefits from third parties. The tendencies to monitor, spread, and manage each other's reputation help explain the abundance of human cooperation with unrelated stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
105
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 143 publications
(108 citation statements)
references
References 113 publications
(145 reference statements)
2
105
0
1
Order By: Relevance
“…Further, more recent advances on SET find that events that remind individuals of resource scarcity, spur more competitive, self-focused, and thus Market Pricing types of interactions (Roux, Goldsmith, & Bonezzi, 2015). The advent of I-focused interactions is consistent with our finding that the PC disruption stage was followed by a period of relational discord (Equality Matching) in the repair stage, which is consistent with SET's emphasis on the role of competition for status and social recognition through gossip (Blau, 1964;Wu, Balliet, & Van Lange, 2016a). Our findings revealed that social discord was major processes during PC renegotiation/repair, which implies that that, at least in the context of organizational change, the restoration of one's personal PC is inextricably tied to that of others.…”
Section: Dynamic Phase Model Of Psychological Contracting Reflected Isupporting
confidence: 86%
“…Further, more recent advances on SET find that events that remind individuals of resource scarcity, spur more competitive, self-focused, and thus Market Pricing types of interactions (Roux, Goldsmith, & Bonezzi, 2015). The advent of I-focused interactions is consistent with our finding that the PC disruption stage was followed by a period of relational discord (Equality Matching) in the repair stage, which is consistent with SET's emphasis on the role of competition for status and social recognition through gossip (Blau, 1964;Wu, Balliet, & Van Lange, 2016a). Our findings revealed that social discord was major processes during PC renegotiation/repair, which implies that that, at least in the context of organizational change, the restoration of one's personal PC is inextricably tied to that of others.…”
Section: Dynamic Phase Model Of Psychological Contracting Reflected Isupporting
confidence: 86%
“…reputational information) could serve as such an IV. Future research might also examine if the effect of partner reputational information on own cooperation (Wu, Balliet, & Van Lange, ) only occurs through expectations of partner cooperation, and then test the mediating effect of expectations on the relation between SVO and cooperation (also including the IV in the model). This approach could address another limitation of the current meta‐analysis: because the meta‐analytic structural equation model was a just identified (saturated) path model, and contained no degrees of freedom, we could not evaluate the model's fit.…”
Section: Limitationsmentioning
confidence: 99%
“…Our second goal was to replicate the effect of reputation on cooperation (Feinberg et al, 2014;Wu et al, 2016b) and test hypotheses about how reputation fosters cooperation in relatively small and large groups. One perspective predicts that reputation is more effective in larger groups because people prefer the best cooperators as partners, such that larger groups contain more competition for reputation and less chance to be selected as partners (Van Vugt et al, 2007;Barclay, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the theory of competitive altruism posits that people prefer to partner with the best cooperators, who will receive more benefits than less cooperative ones (Barclay and Willer, 2007;Van Vugt et al, 2007). Indeed, prior work reveals that people tend to select and cooperate with partners whose reputation is positive (Capraro et al, 2016), and that reputational cues (e.g., gossip) can effectively promote cooperation (Feinberg et al, 2014; for a review, see Wu et al, 2016b). Thus, we expect more cooperation in a situation with reputation-based partner choice than in an anonymous situation (Hypothesis 2).…”
Section: Introductionmentioning
confidence: 99%